(untitled) (NAU Journal of Technology and Vocational Education, 2026)
disposal pathways in urban Nigeria, with evidence from Tudun-Kauri and Angwa-Maina communities in Nasarawa State. A descriptive survey design was adopted, utilizing a structured instrument, titled Refuse Disposal and Health Impact Questionnaire (RDHIQ). This was administered to a sample of households and community residents. Three research questions with iots corresponding null hypotheses were used to collect data. Data collected were analyzed using descriptive statistics, while inferential techniques were employed to test the study hypotheses. Findings indicate that waste disposal is predominantly characterized by open dumping, open burning, and indiscriminate discharge into drainage channels and water bodies. These practices are associated with increased incidence of waste-related diseases, including malaria, typhoid fever, cholera, and dysentery. Key constraints identified include inadequate waste collection infrastructure, irregular public sector intervention, low levels of environmental health awareness, and weak enforcement of sanitation regulations. The study concludes that prevailing waste management practices pose significant risks to public health and environmental sustainability. It recommends the development of integrated waste management systems, provision of designated disposal facilities, routine waste evacuation, community-based sanitation initiatives, and strengthened regulatory enforcement. Implementation of these measures is critical to reducing disease burden and improving health outcomes in urban communities.